Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 30182 by abdo imad last updated on 17/Feb/18

find ∫_2 ^3    ((√(x+1))/(x(√(1−x))))dx .

find23x+1x1xdx.

Commented by abdo imad last updated on 21/Feb/18

let put (√((x+1)/(x−1))) =t ⇔((x+1)/(x−1)) =t^2   ⇔x+1=−t^2  +t^2 x⇔  (1−t^2 )x=−t^2 −1 ⇔x= ((−t^2 −1)/(−t^2 +1))=((t^2  +1)/(t^2 −1))=1+(2/(t^2 −1))⇒  (dx/dt) =((−4t)/((t^2 −1)^2 )) ⇒I= ∫_(√3) ^(√2)    t ((t^2 −1)/(t^2 +1)) ((−4t)/((t^2 −1)^2 ))dt  =4 ∫_(√2) ^(√3)    (t^2 /((t^2 +1)(t^2 −1)))dt= 4 ∫_(√2) ^(√3)   ((t^2 −1+1)/((t^2 +1)(t^2 −1)))dt  =4 ∫_(√2) ^(√3)    (dt/(t^2 +1)) +4 ∫_(√2) ^(√3)   (dt/((t^2 +1)(t^2 −1))) we have  ∫_(√2) ^(√3)   (dt/(1+t^2 ))=arctan((√3)) −arctan((√2)) and  ∫_(√2) ^(√3)      (dt/((t^2 +1)(t^2 −1)))=(1/2)∫_(√2) ^(√3) ( (1/(t^2 −1)) −(1/(t^2 +1)))dt  =(1/2) ∫_(√2) ^(√3)   (dt/(t^2 −1)) −(1/2) (arctan((√(3))) −arctan(√2)))  =(1/2)∫_(√2) ^(√3) ((1/(t−1)) −(1/(t+1)))dt −(1/2)(....)  =(1/2)[ln∣((t−1)/(t+1))∣]_(√2) ^(√3)  −(1/2)(...) ⇒  I=4(artan((√3))−arctan((√2))) +2 ∫_(√2) ^(√3)   (dt/(t^2 −1))dt   −2(arctan((√3))−arctan((√2)))  =2(arctan((√3))−arctan((√2))) +ln∣(((√3) −1)/((√3)+1))∣−ln∣(((√2) −1)/((√2) +1))∣  .

letputx+1x1=tx+1x1=t2x+1=t2+t2x(1t2)x=t21x=t21t2+1=t2+1t21=1+2t21dxdt=4t(t21)2I=32tt21t2+14t(t21)2dt=423t2(t2+1)(t21)dt=423t21+1(t2+1)(t21)dt=423dtt2+1+423dt(t2+1)(t21)wehave23dt1+t2=arctan(3)arctan(2)and23dt(t2+1)(t21)=1223(1t211t2+1)dt=1223dtt2112(arctan(3)arctan2))=1223(1t11t+1)dt12(....)=12[lnt1t+1]2312(...)I=4(artan(3)arctan(2))+223dtt21dt2(arctan(3)arctan(2))=2(arctan(3)arctan(2))+ln313+1ln212+1.

Commented by abdo imad last updated on 21/Feb/18

forgive... the Q is find ∫_2 ^3    ((√(x+1))/(x(√(x−1)))) dx .

forgive...theQisfind23x+1xx1dx.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com